Analysis of changes in population's cross-city travel patterns in the pre- and post-pandemic era: A case study of China. (March 2022) - Wang, Xuyang; Pei, Tao; Li, Kaixi; Cen, Yan; Shi, Miao; Zhuo, Xian; Mao, Tianyu
Abstract: The coronavirus disease (COVID-19) outbreak has immensely changed people's travel behaviour. The changes in travel behaviour have had a huge impact on different industries, such as consumption, entertainment, commerce, office, and education. This study investigates the impact of COVID-19 on population travel patterns from three aspects: total trips, travel recovery degree, and travel distance. The result indicates that COVID-19 has reduced the total number of cross-city trips and flexible non-work travel; in the post-pandemic era, cross-city travel is mainly short-distance (distance <100 km). This study has significant policymaking implications for governments in countries where the population shares a similar change in travel behaviour.